Prognostic role of lymph node metastasis in early gastric cancer - Zheng, Zhixue; Liu, Yiqiang; Bu, Zhaode; Zhang, Lianhai; Li, Ziyu; Du, Hong; Ji, Jiafu (Chinese Journal of Cancer Research; Vol 26, No 2 (April 26, 2014): Chinese Journal of Cancer Research, 2014)
Objective: To clarify the relationship between clinicopathological features and lymph node metastasis and to propose the potential indications of lymph node metastasis for prognosis in early gastric cancer (EGC) patients. Methods: We retrospectively observed 226 EGC patients with lymph node resection, and analyzed the associations between lymph node metastasis and clinicopathological parameters using the chi-square test in univariate analysis and logistic regression analysis in multivariate analysis. Overall survival analysis was determined using the Kaplan-Meier and log-rank test. We conducted multivariate prognosis analysis using the Cox proportional hazards model. Results: Of all the EGC patients, 7.5% (17/226) were histologically shown to have lymph node metastasis. The differentiation, lymphovascular invasion and depth of invasion were independent risk factors for lymph node metastasis in EGC. The 5- and 10-year survival rates were significantly lower in patients with lymph node metastasis than in those without and the patients also had shorter progress-free survival time. Lymph node metastasis and tumor size were independent prognostic factors for EGC. The status of the lymph nodes was a significant factor in predicting recurrence or metastasis after surgery. Conclusions: The undifferentiated carcinoma and lymphovascular and/or submucosal invasion were associated with a higher incidence of lymph node metastasis in EGC patients, whom need to perform subsequent D2 lymphadenectomy or laparoscopic lymph node dissection and more rigorous follow-up or additional chemotherapy/radiation after D2 gastrectomy for poor prognosis and high recurrence/metastasis rate.